(untitled) (FIG Joint Land Administration Conference, 2025)
This study analyzes territorial management in the "New Caximba Neighborhood Climate Risk Management" project in Curitiba, Paraná, Brazil, an intervention aimed at the requalification of precarious settlements in an environmentally sensitive area vulnerable to climatic risks. The project involves family resettlement and infrastructure implementation, with land management, especially in the Resettlement Action Plan (PAR) phase, being a critical element. The research investigated, identified, and critically analyzed the methodological approach employed in the conception and initial phases of the PAR. It was found that the actions of the Curitiba Research and Urban Planning Institute (IPPUC) and the Curitiba Popular Housing Company (COHAB) were guided by an interaction between the Land Administration Domain Model (LADM), for information structuring, and the Fit-For-Purpose (FFP) approach, for adapting surveys in a context of informality. The analysis of this practical application allowed for an evaluation of the innovation and adaptability of territorial management, contributing to urban planning and land administration in Brazil. The research sought to fill a gap regarding the joint application of LADM and FFP in large-scale urban requalification projects. This approach, which structured data and adapted surveys, resulted in an agile and inclusive resettlement that prioritized sustainability and community participation. This generated subsidies to improve future similar interventions and reinforced the importance of territorial management for the long-term sustainability of the project.